Methodology of a new inflammatory arthritis registry: TReasure - Kalyoncu, Umut; Tascilar, Etem Koray; Ertenli, Ali Ihsan; Dalkilic, Huseyin Ediz; Bes, Cemal; Kucuksahin, Orhan; Kiraz, Sedat (Tubitak Scientific & Technological Research Council Turkey, 2018)
Background/aim: The TReasure registry, created in 2017, is an observational multicenter cohort that includes inflammatory arthritis patients. This article reviews the methodology and objectives of the TReasure registry established to collect data from rheumatoid arthritis (RA) and spondyloarthritis (SpA) patients. Methodology: Fifteen rheumatology centers in Turkey will contribute data to the TReasure database. The actual proprietor of the database is the Hacettepe Rheumatology Association (HRD) and Hacettepe Financial Enterprises. Pharmaceutical companies that operate in Turkey (in alphabetical or er), Abbvie, Amgen, BMS, Celltrion Healthcare, Novartis, Pfizer, Roche, and UCB, support the TReasure registry. TReasure is a web-based database to which users connect through a URL (https://www.trials-network.org/treasure) with their unique identifier and passwords provided for data entry and access. TReasure records demographic and clinical features, comorbidities, radiology and laboratory results, measures of disease activity, and treatment data. Discussion: TReasure will provide us with various types of data, such as a cross-sectional view of the current nationwide status of the patients currently receiving these treatments, and retrospective data as much as allowed by the participating centers' records. Finally, a high-quality prospective dataset will be built over the ensuing years from patients with a new diagnosis of RA or SpA.
Keywords: Rheumatoid arthritis; spondyloarthritis; disease-modifying antirheumatic drugs; registry; TReasure